The Role of the Head of School in the Implementation of Two Curriculums in the Basic School of MI Muhammadiyah Ngombakan, Polokarto, Sukoharjo - Nurul ‘Ilmi Azizah, Annafi; Hidayatullah, Alfian; Rona Apriliana , Alfina; Ummu Azzahro, Fatihah; Az Zahra, Fatimah (CV Kalimasada Group, 2024)
The study aims to evaluate the implementation of the secondary education curriculum in Madrasah Ibtidaiyah Muhammadiyah Ngombakan. The research methods used are qualitative, with a focus on planning, organization, leadership, evaluation and monitoring as well as curriculum follow-up. Data is collected through observations, interviews and documentation. The research subjects are the Head of the School and the Chief of the Curriculum. This research contributes to a further understanding of the implementation of basic education curricula and provides recommendations for future improvements. Based on the results of the research showed that Madrasah Ibtidaiyah Muhammadiyah Ngombakan successfully implemented two curricula well, reflecting the ability to adapt and respond to change in education. Structured curriculum administration processes, clear leadership systems, and periodic evaluations are a strong basis for providing quality education.